Outcomes of a National Institute of Allergy and Infectious Diseases Workshop on Understanding HIV-Exposed but Seronegative Individuals - Young, Janet M. (Mary Ann Liebert, Inc., 2011)
The fascinating conundrum that some individuals who are exposed to HIV in ways that would make viral transmission highly likely, yet are able to remain uninfected, has been appreciated for many years. As early as the late 1980s, reports of such individuals began appearing in the HIV/AIDS literature. Despite the critical importance of understanding possible mechanisms of natural HIV resistance for developing effective prevention strategies, numerous obstacles have prevented this essential area of scientific exploration from moving forward. The Workshop held on July 8–9, 2010 and supported by the Office of AIDS Research (OAR), the National Institute of Allergy and Infectious Diseases (NIAID), and the National Institute on Drug Abuse (NIDA) at the NIH hosted 200 participants and utilized the expertise of 42 AIDS researchers as invited speakers, session chairs, and discussion leaders for presentations and breakout sessions in an attempt to remove some of those obstacles. Accomplishments of the participants included developing a consensus for a new general term for the field, HIV-exposed seronegative (HESN), while recognizing the necessity to identify and utilize secondary descriptive criteria such as exposure level, risk group, duration of seronegativity, or natural resistance. Three key questions for future research were also identified by the group: (1) What is different in HESN versus those who get infected? (2) What is the immune response in HESN and is it just a marker of exposure or a correlate of protection? (3) What are the HESN host factors that help HESN resist infection? This report briefly summarizes the presentations, and describes future directions for addressing these questions and challenges.